The Relationship between Psychological Hardiness, Coping Styles, Emotion Regulation, and Tendency toward Addiction among Students - H. Choubchian Langarudi; M.R. Zarbakhsh, Ph.D. (خانواده و پژوهش, 2018)
This research was conducted to investigate the relationship between psychological hardiness, coping styles, emotion regulation, and tendency toward addiction among senior high school students in Langarud. The method of the study was descriptive and correlational and the statistical population of the study comprised 2040 high schoolers in academic year 2015-2016 from among them 200 students were selected via random cluster sampling method. The instruments included Psychological Hardiness Scale (Kobasa, 1970), Billings & Moos Coping Checklist (1984), Cognitive Emotion Regulation Questionnaire (Garnefski & Kraaij, 2006), and Addiction Potential Scale (Zargar, 2006). The obtained data were analyzed by using step-wise regression and pearson correlation. The results showed that there was a significant relationship between psychological hardiness, emotion regulation, physical inhibition (a component of coping strategies), and tendency toward addiction. Furthermore, psychological hardiness and adaptive emotion regulation strategies accounted for 32.2% and 4.2% of the variance in tendency toward addiction, respectively.